A stepwise energy level doping structure for improving the lifetime of phosphorescent organic light-emitting diodes. Issue 16 (5th April 2017) - Song, Wook; Kim, Taekyung; Lee, Yoonkyoo; Lee, Jun Yeob
Abstract : A stepwise energy level doping structure for improving the lifetime of organic light-emitting diodes was developed by doping two emitters with different energy levels in the same host material as separated emitting layers. Abstract : A stepwise energy level doping structure for improving the lifetime of organic light-emitting diodes was developed by doping two emitters with different energy levels in the same host material as separated emitting layers. A hole-trapping phosphorescent emitter was doped in the emitting layer close to the electron transport layer and an electron-trapping thermally activated delayed fluorescent emitter was doped in the emitting layer close to the hole transport layer to show stepwise energy levels between emitting materials in the same host. The stepwise energy level doping structure improved the lifetime of organic light-emitting diodes through suppressed triplet–triplet annihilation and triplet–polaron annihilation by emission zone control and carrier confinement. Moreover, a high quantum efficiency close to 20% was realized in both green and blue organic light-emitting diodes in addition to the improved lifetime. This is the first work reporting both high quantum efficiency close to 20% and elongated lifetime simultaneously.